Season of Birth Predicts Emotional and Behavioral Regulation in 18-Month-Old Infants: Hamamatsu Birth Cohort for Mothers and Children (HBC Study) - Asano, Ryosuke; Tsuchiya, Kenji J.; Harada, Taeko; Kugizaki, Yumeno; Nakahara, Ryuji; Nakayasu, Chikako; Okumura, Akemi; Suzuki, Yukiko; Takagai, Shu; Mori, Norio; Takei, Nori; , for Hamamatsu Birth Cohort (HBC) Study Team (Frontiers in Public Health, 2016)
Background: Previous research has demonstrated that the season of birth may predict development of emotional and behavioral regulation during childhood or adolescence. This study examined whether the season of birth predicts effortful control (i.e., the ability to voluntarily choose course of actions during conflict and to plan for the future) and aggression (i.e., the use of physical force and expression of anger toward others) in 18-month-old infants. Methods: Participants included 885 infants who were enrolled in the Hamamatsu Birth Cohort for Mothers and Children in Hamamatsu, Japan. Seasons of birth were categorized into winter (December, January, and February), spring (March, April, and May), summer (June, July, and August), and autumn (September, October, and November). At 18 months of age, effortful control was assessed using the Early Childhood Behavior Questionnaire, and aggression was measured using the Cardiff Infant Contentiousness Scale. Structural equation modeling analysis with measurement and structural equations was conducted to test our prediction. Results: Effortful control was higher in infants born in spring (B = 0.095, 95% CI [0.014 to 0.175], p = 0.021,  = 0.146) and summer (B = 0.078, 95% CI [0.001 to 0.156], p = 0.049,  = 0.118) than in those born in winter. In addition, aggression was lower in those born in spring (B = −0.286, 95% CI [−0.551 to −0.021], p = 0.035,  = −0.135) than those born in winter, even after controlling for seven covariates. Conclusion: The findings suggest that season of birth may determine development of emotional and behavioral regulation skills during early infancy. Future research should pay more attention to the underlying mechanisms of the effects of birth season on development of emotional and behavioral regulation during infancy.